Non-Hodgkin Lymphoma and Pleural Mesothelioma in a Person Exposed to Asbestos - Claudio BIANCHI; Tommaso BIANCHI (Federation of Turkish Pathology Societies, 2018)
Non-Hodgkin lymphoma and pleural mesothelioma may co-exist in the same patient. A large cell non-Hodgkin lymphoma of the inguinal lymph nodes was diagnosed in a 73-year-old woman. The patient was treated by chemotherapy. She did not receive radiotherapy. The patient had been exposed to asbestos having worked in a cotton mill and in a distillery. Four years after the diagnosis of lymphoma, she presented with a left pleural effusion. Large biopsies of the pleura showed a malignant mesothelioma, biphasic type, and pleural plaques. Epidemiological studies about the asbestos-lymphoma relationship gave conflicting results. The lymphoma-mesothelioma association is not exceptional, and suggests that asbestos plays a role in the etiology of both malignancies.